The Influence of Employee Engagement on Organizational Profit - Dawwas, Mohammed I. F. (2010)
This study is designed to determine the relationship between employee engagement, and organizational profit. In addition the study examines whether there is a significant difference in mean score on employee engagement between males and females in Palestinian telecommunication company. The scope of the study is limited to managers in Palestinian Telecommunication Company. The results showed statistically significant positive relationships between employee engagement and organization performance. It also shows that there is a significant difference in employee engagement between male and female in Palestinian Telecommunication Company.